Prevalence and trends of overweight and obesity in older adults from 10 European countries from 2005 to 2013 - Peralta, Miguel (2019)
Aims: Overweight and obesity are clinical public-health concerns worldwide. Amongst older adults, the prevalence of overweight and obesity is considered high. The purpose of this study was to provide current data regarding the prevalence and trends of overweight and obesity of adults from 2005 to 2013 in 10 European countries. Methods: The data used in the present study were derived from the first, second, fourth and fifth waves of the Survey of Health, Ageing and Retirement in Europe. The present study includes individuals aged ⩾50 years from 10 European countries. Body mass index (BMI) was calculated from self-reported height and weight (kg/m2). Results: The general prevalence of overweight (BMI ⩾25 kg/m2) was slightly above 60% and remained stable between 2005 (60.1%, 95% confidence interval (CI): 59.3–60.9%) and 2013 (60.3%, 95% CI: 59.7–60.9%). On the other hand, the prevalence of obesity (BMI ⩾30 kg/m2) increased significantly (1.6 points, 95% CI: 0.7–2.6) from 17.5% in 2005 to 19.2% in 2013. Although the prevalence of obesity increased in most countries, the only significant increase was observed in Germany (5.8 points, 95% CI: 1.8–9.9). Spain was the only country where the prevalence of obesity decreased significantly (−4.7 points, 95% CI: −8.8 to −0.5). Sex and age differences are reported. Conclusions: Although the prevalence of overweight was stable, the prevalence of obesity rose. Based on the data currently available for Europe, the prevalence of obesity in European older adults has already reached epidemic proportions, which reinforces the need for the development of effective healthy lifestyle programs.